2006
DOI: 10.1021/bi0608562
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of ATP Hydrolysis by Monomeric Kinesin Eg5

Abstract: Kinesin-5 family members including human Eg5/KSP contribute to the plus-end-directed force necessary for the assembly and maintenance of the bipolar mitotic spindle. We have used monomeric Eg5-367 in the nucleotide-free state to evaluate the role of microtubules at each step in the ATPase cycle. The pre-steady-state kinetic results show that the microtubule-Eg5 complex binds MgATP tightly, followed by rapid ATP hydrolysis with a subsequent slow step that limits steady-state turnover. We show that microtubules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 63 publications
(138 reference statements)
8
42
1
Order By: Relevance
“…ATP Hydrolysis Is Rate Limiting for Eg5-513-For monomeric Eg5, the rate-limiting step in the ATPase cycle was proposed to be the coupled step of phosphate release and detachment from the MT (30,33). The data presented here suggest that the rate-limiting step for dimeric Eg5 is altered from that of the monomer.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…ATP Hydrolysis Is Rate Limiting for Eg5-513-For monomeric Eg5, the rate-limiting step in the ATPase cycle was proposed to be the coupled step of phosphate release and detachment from the MT (30,33). The data presented here suggest that the rate-limiting step for dimeric Eg5 is altered from that of the monomer.…”
Section: Discussionmentioning
confidence: 81%
“…However, on the MT, ATP binding is tight, substrate productively proceeds through ATP hydrolysis, and the rates of all the individual steps in the mechanochemical cycle are accelerated (30). The MT-activated ATPase cycle concludes with a conformational change of the motor domain in relation to the MT, termed "rolling" (29), followed by the rate-limiting event in the cycle, the coupled action of phosphate (P i ) release, and motor detachment from the MT (29,30,33).In vivo the individual Eg5 motor domains probably do not function independently; therefore, analysis of a higher order oligomeric structure is necessitated. Indeed, previous analysis of dimeric Eg5, Eg5-513, has indicated that two conjoined motor domains exhibit cooperativity in vitro (34,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis was performed to generate E358(wt), E368(R234K), and E368(S233C/ R234K) (supplemental Table S2), and these mutations were confirmed by DNA sequencing. Each construct was co-transformed into B834(DE3) cells with pRIL (Stratagene), and the kinesin-5 protein was expressed and purified in the nucleotidefree state as described previously (9,20,21). Briefly, MgATP was excluded from all column chromatography buffers, and the enriched kinesin-5 fractions from the nickel-nitrilotriacetic acid agarose column (Qiagen) were pooled, incubated with 10 mM EDTA, and buffer-exchanged using desalting columns (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…This structural arrangement allows the enzyme to slide along adjacent MTs during mitosis, thus contributing to the plus enddirected force that is necessary for forming and maintaining the mitotic spindle (17,18). Previous studies have kinetically characterized the ATPase mechanism of dimeric (19) and monomeric kinesin-5 in the absence (20) and presence of MTs (9,10,21). The results of these kinetic studies have been correlated to changes in the neck linker orientation of kinesin-5 for force generation and processive motility along the MT (10,19,22).…”
mentioning
confidence: 99%